“I think I can see from another perspective now” – Short-Term Study Abroad and Intercultural Development - Wai Meng Chan (Journal of Linguistics and Language Teaching)
Foreign language study abroad has the potential to contribute to learners’ culture learning and the cultivation of their intercultural competence, as it gives them first-hand experience in the target-language country and allows them to discover and partake in the local community’s sociocultural practices. This article presents a study of the impact of two short-term study abroad programmes in Germany on the intercultural development of German-language students from a Singapore university language centre. The study adopted a mixed-methods approach and collected both quantitative and qualitative data through pre- / post-programme questionnaires, journals, interviews, activity observations and document inspections. The data were analysed based on Byram’s (1997, 2008) model of intercultural competence, as well as Lave & Wenger’s (1991) Situated Learning Theory and their notion of legitimate peripheral participation. The findings suggest that the study abroad programmes, or “In-Country Language Immersions”, benefited learners in the development of the knowledge, attitudes and skills needed for the cultivation of critical cultural awareness and intercultural competence. It was further found that such positive development is often precipitated by the learners’ legitimate peripheral participation in the local communities, although it is dependent on their motivation and willingness to take up such opportunities for interaction and participation.